1999
DOI: 10.1007/s004230050191
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral resection of advanced colorectal carcinoma

Abstract: An identical surgical risk and survival rates for curative resection, equally as good as those seen with conventional, non-extended procedures, justify the liberal use of multivisceral resection in the surgical treatment of colorectal carcinomas directly invading neighbouring organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
93
3
16

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 16 publications
15
93
3
16
Order By: Relevance
“…In our study, malignant invasion was histologically confirmed in 60.9% of patients presenting with the primary tumor adherent to the adjacent organs. This finding is similar to previous reports (5,6). On the other hand, some previous studies demonstrated that adhesions between tumor and other organs harbor malignant cells in 25-40% of cases, which are lower rates compared with our study (2,7,8).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, malignant invasion was histologically confirmed in 60.9% of patients presenting with the primary tumor adherent to the adjacent organs. This finding is similar to previous reports (5,6). On the other hand, some previous studies demonstrated that adhesions between tumor and other organs harbor malignant cells in 25-40% of cases, which are lower rates compared with our study (2,7,8).…”
Section: Discussionsupporting
confidence: 92%
“…The affected organ should be resected en bloc with a safe margin of normal tissue. Patients who undergo a marginnegative multivisceral resection present survival that is similar to that of individuals with no adjacent organ involvement, on a stage-matched basis (6,7) . Locally advanced cancer of the right colon that adheres to the proximal duodenum or head of the pancreas presents a challenge, even for skilled surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Antes de realizar uma ressecção multivisceral, a condição clínica do paciente e a presença ou não de metástases à distância devem ser consideradas. A taxa de mortalidade das ressecções em bloco é de 3% 3 . As ressecções multiviscerais em monobloco, associam-se com tempo de sobrevivência médio de 40 meses e taxa de sobrevivência em cinco anos livre de doença de 54%.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Já a sobrevivência média do "bypass" paliativo é de nove meses, e da ressecção incompleta, incluindo a ressecção com separação de órgãos é de 11 meses 4 . O longo período de sobrevivência após ressecções multiviscerais, pode ser explicado pela ausência de metástases em linfonodos regionais (N0), em 45% dos casos 5 , A literatura consultada, mostra que se o paciente tiver condições clínicas adequadas e não apresentar metástases à distân-cia, a ressecção multivisceral é o tratamento de escolha, mesmo quando a operação associada tem a magnitude e complexidade de uma duodenopancreatectomia [1][2][3][4][5] . O papel da quimioterapia adjuvante no tratamento de tumores localmente invasivos é incerto 4 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
See 1 more Smart Citation